Localized Relapse of Primary Plasma Cell Leukaemia in the Central Nervous System - Christian W. Eskelund; Niels Frost Andersen (Case Reports in Hematology)
Primary plasma cell leukaemia (pPCL) is a rare and aggressive form of plasma cell malignancies with a very poor prognosis. Compared to other plasma cell malignancies the tendency to extramedullary spread is increased; however central nervous system (CNS) involvement is rare and only reported in few cases. We report the case of a 61-year-old man who was diagnosed with pPCL and achieved a complete remission after autologous stem cell transplantation but had a relapse in the CNS without systemic disease.